Implications of not matching to a first-choice discipline: a family medicine perspective - Woloschuk, Wayne; Myhre, Douglas; Dickinson, James; Ross, Shelley (Canadian Medical Education Journal, 2017)
Background: Family medicine is often selected as an alternate career choice by medical students who do not match to their first choice discipline. Consequently, family medicine residency programs accept and train some residents who prepared for and intended a career in another specialty. The implications of this warrant investigation. Methods: Graduates (2006-2011) of Albertan family medicine residency programs were surveyed to examine differences between physicians who indicated family medicine was their first choice discipline and those who indicated that it was not their first choice. Survey questions targeted practice location, preparedness for practice, perceptions of family medicine, lifestyle satisfaction, and well-being. Principal components analysis was used to examine the factor structure of our survey items and ANOVA and Chi square were used to compare mean scores and proportions, respectively. Results: The overall response rate was 47.2% (307/651). Most (263) respondents reported that family medicine was their first choice discipline (yes-group); 42 respondents indicated that it was not (no-group) and two did not answer. The two groups were similar demographically. The no-group reported significantly lower mean scores on perceptions of family medicine. There were no significant differences between the two groups in their preparedness for practice and measures of lifestyle satisfaction and well-being. Conclusion: Irrespective of their perceptions of the discipline, the respondents who did not match to their first choice discipline found family medicine to be a viable career option.